Healthy Bakery Business Plan - Asadova, Zahra (ADA University, 2022)
The catering industry is at the phase of recovery from the post-pandemic repercussions. While from the supply side firms need to recover from the Covid-19 crisis, from the demand one consumers’ have started asking for a more ethic, in terms of social, environmentally sustainable, and healthy consumption. Answers from the industry are coming but are still insufficient: most of the times firms sustainability actions are too poor to make one of the most polluting and exploiting industries “greener”, and as far as health issues are concerned, some brands are launching capsules that do not completely satisfy customers requests. Healthy Bakery will fill the gap in the supply side by opening a store in Baku, Azerbaijan. The sections of the present business plan aim at showing the feasibility and the value of our business idea for any stakeholder category. Here is provided with a summary of the overall content of the plan.
Keywords: Catering industry; Healthy Bakery; Business plan; Business